Analisis Perbandingan Kinerja Keuangan Terhadap Profitabilitas Bank Konvensional dan Bank Syariah di Indonesia: (Studi Kasus Pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2024) - Arip Budi Setiawan; Ratu Anggi Triani (Baashima : Jurnal Bisnis Digital, Akuntansi, Kewirausahaan, dan Manajemen, 2026)
This study aims to analyze differences in profitability between conventional and Islamic banks in Indonesia during the 2020-2024 period. The novelty of the study lies in an observation period that covers the pandemic, economic recovery, and accelerated banking digitalization. A comparative quantitative approach was applied using secondary data from the annual reports of 10 banks, consisting of five conventional banks and five Islamic banks. Profitability was measured using Return on Assets (ROA). Fifty observations were analyzed through descriptive statistics, the Shapiro-Wilk normality test, and the Mann-Whitney U test because one group was not normally distributed. The results show that Islamic banks recorded an average ROA of 2.9060%, higher than the 2.0844% average of conventional banks. Nevertheless, the Mann-Whitney test produced a significance value of 0.449, indicating that the hypothesis of a profitability difference was not supported. Therefore, differences in operating models did not produce a statistically significant profitability difference during the study period. The findings indicate that asset management efficiency, financing or credit quality, and cost control are more relevant in explaining banks ability to generate profits.